1991
DOI: 10.1038/350678a0
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity NGF binding requires coexpression of the trk proto-oncogene and the low-affinity NGF receptor

Abstract: Nerve growth factor (NGF) interacts with two different low-affinity receptors that can be distinguished by affinity crosslinking. Reconstitution experiments by membrane fusion and transient transfection into heterologous cells indicate that high-affinity NGF binding requires coexpression and binding to both the low-affinity NGF receptor and the tyrosine kinase trk gene product. These studies reveal a new growth factor receptor-mediated mechanism of cellular differentiation involving trk and the low-affinity NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
508
2
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,139 publications
(532 citation statements)
references
References 79 publications
21
508
2
1
Order By: Relevance
“…TrkA was rapidly shown to mediate the known responses to NGF, such as neurite outgrowth and neuronal survival (Lee et al, 2001a;Lykissas et al, 2007), whereas the precise biological role of p75 NTR remained misunderstood. p75 NTR was shown to collaborate with TrkA to form high-affinity sites for NGF binding (Hempstead et al, 1991). In addition, p75 NTR was shown to alter the ligand specificity of other Trk receptors.…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…TrkA was rapidly shown to mediate the known responses to NGF, such as neurite outgrowth and neuronal survival (Lee et al, 2001a;Lykissas et al, 2007), whereas the precise biological role of p75 NTR remained misunderstood. p75 NTR was shown to collaborate with TrkA to form high-affinity sites for NGF binding (Hempstead et al, 1991). In addition, p75 NTR was shown to alter the ligand specificity of other Trk receptors.…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…April 1992 Hempstead et al reported that the high-affinity receptor for nerve growth factor (NGF) requires formation of an heteromeric complex composed of the rrk tyrosine kinase proto-oncogene product and another molecule of low-affinity receptor for NGF [23]. Low affinity binding sites for HGF were present in both HGF-responsive epithelial cells and also in HGF-nonresponsive mesenchymal cells.…”
Section: Lettersmentioning
confidence: 99%
“…The p75 gene, when transfected into nonneuronal cells, was shown to generate low a nity NGF binding sites, while expression in neuronal cells induced NGF-mediated cell di erentiation (Hempstead et al, 1989;Johnson et al, 1986;Matsushima and Bogenmann, 1990;Pleasure et al, 1990). Complex formation between p75 and trkA was observed, thus enhancing the NGF signal (Hempstead et al, 1991;Verdi et al, 1994). However, the p75 receptor belongs to the family of tumor necrosis factor receptors, and over expression in brain-derived cell lines induced apoptosis in the absence of NGF (Chao, 1992;Rabizadeh et al, 1993).…”
Section: Introductionmentioning
confidence: 99%